Monashia flava gen. Nov., sp. nov., An actinobacterium of the family Intrasporangiaceae - Azman, A.S.; Zainal, N.; Mutalib, N.S.A.; Yin, Wai Fong; Chan, Kok Gan; Lee, L.H. (Society for General Microbiology, 2016)
A novel actinobacterial strain, MUSC 78T, was isolated from a mangrove soil collected from Peninsular Malaysia. The taxonomic status of this strain was determined using a polyphasic approach. Comparative 16S rRNA gene sequence analysis revealed that strain MUSC 78T represented a novel lineage within the class Actinobacteria. Strain MUSC 78T formed a distinct clade in the family Intrasporangiaceae and was related most closely to members of the genera Terrabacter (98.3–96.8 % 16S rRNA gene sequence similarity), Intrasporangium (98.2– 96.8 %), Humibacillus (97.2 %), Janibacter (97.0–95.3 %), Terracoccus (96.8 %), Kribbia (96.6 %), Phycicoccus (96.2–94.7 %), Knoellia (96.1–94.8 %), Tetrasphaera (96.0–94.9 %) and Lapillicoccus (95.9 %). Cells were irregular rod-shaped or cocci and stained Grampositive. The cell-wall peptidoglycan type was A3γ, with LL-diaminopimelic acid as the diagnostic diamino acid. The main cell-wall sugar was mannose and lower amounts of galactose and rhamnose were present. The predominant menaquinone was MK-8(H4). The polar lipid profile consisted of phosphatidylglycerol, phosphatidylinositol, phosphatidylethanolamine, diphosphatidylglycerol and phosphoglycolipid. The predominant fatty acids were iso-C15: 0, anteiso-C15: 0 and iso-C16: 0.The DNA G+C content was 73.1 mol%. Based on this polyphasic study, MUSC 78T exhibited phylogenetic and phenotypic differences from members of the genera of the family Intrasporangiaceae, and therefore a novel species of a new genus, Monashia flava gen. nov., sp. nov., is proposed. The type strain of Monashia flava is MUSC 78T (=DSM 29621T=MCCC 1K00454T=NBRC 110749T).